Burns Care in Sub‑Saharan Africa: Experience from a Trauma Registry in Nigeria – An Observational Study - Ibeanusi, Sydney E.; Kejeh, B. (Nigerian Journal of Orthopaedics and Trauma, 2018)
Background: Burns is quite common and often associated with deleterious consequences. The incidence, mortality and morbidity from burns are decreasing in most developed countries over the years, but in the developing countries, the burden of burn injuries continue to pose a significant challenge. Various factors have been attributed to this persisting trend. This study aim is to highlight the pattern of presentation, care and outcome of injuries from burns from a regional trauma registry in Nigeria. Methods: Retrospective evaluation of data from a regional trauma registry in Port Harcourt Nigeria prospectively collected over a seven-year period (from January 2007 to December 2013). Descriptive and inferential statistics of the results are presented. Results: The result showed that 601 cases of burns were recorded during the period under observation. Males between the age group (20-29) years were the most involved (n = 223 {37.1%}) and flame burns (n = 380 {63.2%}) arising mainly from explosions of petroleum products (n = 333 {55.4%}) was the most commonly seen. The overall mortality recorded was 34%, but the median lethal burn surface area at which 50% of the victims died was about 40%. Most of the deaths occurred in the first week following burns. The common early complications were fluid and electrolyte derangement (n = 280 {46.6%}), while burn scarring was a common complication among survivors. Conclusion: Burns remains a significant contributor to high trauma mortality and morbidity in the region. Inadequate infrastructure, human and material resources and some persisting cultural beliefs and practises contribute to the poor outcome of burns.